Diversite et Degre d’Infestation de la Flore Adventice dans les Parcelles Rizicoles du Departement de Man (Cote d’Ivoire) - Benjamin, Kouman Koffi; Frédéric, Kouame Kra; Awa, Toure (European Scientific Journal, ESJ, 2024)
Dans la plupart des zones productrices de riz pluvial de la Côte d’Ivoire notamment le département de Man, les producteurs de riz pluvial sont confrontés aux difficultés telles que l’enherbement. La présente étude vise à contribuer à la connaissance des communautés des adventices et leur degré d’infestation en vue d’une gestion efficiente de ces dernières. La méthode d’approche est une enquête réalisée auprès des riziculteurs et des relevés floristiques sur leurs parcelles ont été réalisés. Ces derniers ont permis d’évaluer les paramètres tels que les fréquences et l’indice d’abondance-dominance. Ainsi, grâce à ces paramètres, le diagramme d’infestation a pu identifier les adventices les plus abondantes. L’inventaire a permis de recenser 88 espèces réparties en 72 genres et 37 familles avec 72,72 % de Dicotylédones. Les familles les mieux représentées sont les Poaceae, les Cyperaceae et les Asteraceae. Les plus régulières et abondantes selon nos relevés sont Ageratum conyzoides Linn. et Calopogonium mucunoides Desv. Les riziculteurs ont identifié, Calopogonium mucunoides Desv. comme étant récurrente et nuisible lorsqu’elle n’est pas maitrisée assez tôt. The disturbance of the environment is at the origin of the destruction of the habitats, it contributes to the loss of the biodiversity and is one of the causes of the change of the flora in a locality. It therefore leads to the transformation of plant associations. The main objective of this study is to research the plant associations in the Banco National Park following village plantations and silvicultural trials due to the search for a methodology specific to African silviculture. To do this, the phytosociological characterization of the former treatment sites and the forest reserve was carried out. The method used is that of synusial phytosociology. The 91 surveys (82 in the former silvicultural treatment sites and 9 in the forest reserve) made it possible to identify 337 species of plants divided into 65 families and 268 genera. The dendrogram resulting from the ascending hierarchical classification of the readings revealed three syntaxa, two of which essentially consist of the readings of the old treatment sites and one of the readings of the forest reserve. No syntaxon contains all the characteristic species of the Turraeantho-Heisterietum association. However, in two syntaxa, the proportion of characteristic species of this association is greater than 50%. 70.59% in the syntaxon to Tarrietia utilis and Cola heterophylla (syntaxon from secondary forests), 52.94% in the syntaxon to Cola chlamydantha and Drypetes chevalieri (syntaxon from the forest reserve). While in the Dacryodes klaineana and Pleiocarpa mutica syntaxon (secondary forest syntaxon), 41% of these characteristic species were recorded. Species characteristic of other forest formations are also poorly represented in the syntaxa (less than 40%). It therefore emerges from this study that Banco National Park remains a forest with Turraeanthus africanus and Heisteria parvifolia.